2021
DOI: 10.1186/s12872-021-02052-z
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in optimal medical therapy after PCI and its influence on clinical outcomes in China

Abstract: Background Limited data were available on the current trends in optimal medical therapy (OMT) after PCI and its influence on clinical outcomes in China. We aimed to evaluate the utilization and impact of OMT on the main adverse cardiovascular and cerebrovascular events (MACCEs) in post-PCI patients and analyzed the factors predictive of OMT after discharge. Methods We collected data from 3812 individuals from 2016.10 to 2017.09 at TEDA Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…22 Based on the evidence of an observation study, the incidence of MACCE in patients after PCI was increased 1.060 times by smoking. 23 Smoking increased the production of clopidogrel active metabolites by inducing CYP1A2 activity. 24 This effect was more notable in high-risk patients, especially those with ACS, a circumstance defined as the "smoking paradox."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Based on the evidence of an observation study, the incidence of MACCE in patients after PCI was increased 1.060 times by smoking. 23 Smoking increased the production of clopidogrel active metabolites by inducing CYP1A2 activity. 24 This effect was more notable in high-risk patients, especially those with ACS, a circumstance defined as the "smoking paradox."…”
Section: Discussionmentioning
confidence: 99%
“…Compared with nonsmokers, smokers seemed to have a higher short‐term mortality rate after PCI 22 . Based on the evidence of an observation study, the incidence of MACCE in patients after PCI was increased 1.060 times by smoking 23 . Smoking increased the production of clopidogrel active metabolites by inducing CYP1A2 activity 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified the final participants for the following reasons. (1) Most existing post-PCI surveys focus on the first 3 years after PCI, and there are fewer data on the follow-up of patients beyond 3 years after PCI ( Zhang et al, 2021 ; Zhang et al, 2023 ). (2) Our pre-survey showed that the success rate of surveying patients more than 10 years after PCI was very low (<20%) due to patient death, change of contact phone number, and unwillingness to cooperate.…”
Section: Methodsmentioning
confidence: 99%